Biomarkers of extracellular matrix turnover in patients with idiopathic pulmonary fibrosis given nintedanib (INMARK study): a randomised, placebo-controlled study. Issue 9 (September 2019) - Maher, Toby M; Stowasser, Susanne; Nishioka, Yasuhiko; White, Eric S; Cottin, Vincent; Noth, Imre; Selman, Moisés; Rohr, Klaus B; Michael, Andreas; Ittrich, Carina; Diefenbach, Claudia; Jenkins, R Gisli; et al.
Summary: Background: A hallmark of idiopathic pulmonary fibrosis is the excess accumulation of extracellular matrix in the lungs. Degradation of extracellular matrix generates free-circulating protein fragments called neoepitopes. The aim of the INMARK trial was to investigate changes in neoepitopes as predictors of disease progression in patients with idiopathic pulmonary fibrosis and the effect of nintedanib on these biomarkers. Methods: In this randomised, double-blind, placebo-controlled trial, patients with a diagnosis of idiopathic pulmonary fibrosis within the past 3 years and forced vital capacity (FVC) of 80% predicted or higher were eligible to participate. Patients were recruited from hospitals, private practices, clinical research units, and academic medical centres. Patients were randomly assigned (1:2) with the use of a pseudo-random number generator to receive oral nintedanib 150 mg twice a day or placebo for 12 weeks in a double-blind fashion, followed by open-label nintedanib for 40 weeks. The primary endpoint was the rate of change in C-reactive protein (CRP) degraded by matrix metalloproteinases 1 and 8 (CRPM) from baseline to week 12 in the intention-to-treat population. The trial has been completed and is registered with ClinicalTrials.gov, number NCT02788474, and with the European Clinical Trials Database, number 2015–003148–38. Findings: Between June 27, 2016, and May 15, 2017, 347 patients were randomly assigned to the nintedanib group (n=116) or to the placebo group (n=231). One patient from the placebo group was not treated owing to a randomisation error. At baseline, mean FVC was 97·5% (SD 13·5) predicted. In the double-blind period, 116 patients received nintedanib and 230 patients received placebo. The rate of change in CRPM from baseline to week 12 was −2·57 × 10 −3 ng/mL/month in the nintedanib group and −1·90 × 10 −3 ng/mL/month in the placebo group (between-group difference −0·66 × 10 −3 ng/mL/month [95% CI −6·21 × 10 −3 to 4·88 × 10 −3 ]; p=0·8146). The adjusted rate of change in FVC over 12 weeks was 5·9 mL in the nintedanib group and −70·2 mL in the placebo group (difference 76·1 mL/12 weeks [31·7 to 120·4]). In patients who received placebo for 12 weeks followed by open-label nintedanib, rising concentrations of CRPM over 12 weeks were associated with disease progression (absolute decline in FVC ≥10% predicted or death) over 52 weeks. In the double-blind period, serious adverse events were reported in eight (7%) patients given nintedanib and 18 (8%) patients given placebo. Grade 3 diarrhoea was reported in two (2%) patients in the nintedanib group and two (1%) patients in the placebo group. No patients had grade 4 diarrhoea. Interpretation: In patients with idiopathic pulmonary fibrosis and preserved lung function, treatment with nintedanib versus placebo for 12 weeks did not affect the rate of change in CRPM but was associated with a reduced rate of decline in FVC. These results suggest that change in CRPM is not a marker of response to nintedanib in patients with idiopathic pulmonary fibrosis. Funding: Boehringer Ingelheim.